Privacy and territoriality in shared bedrooms - Perez, Myla C. (2007., 2007)
The study sought to find out whether privacy and territoriality issues prevailed in selected bedrooms shared by Filipino siblings and how these issues were resolved by the occupants. From this the general perceptions of the respondentson privcy and territorility were derived, analyzed, and compared according to gender. The research underscores the need for local designers to design according to the Filipino lifestyle and needs. In particular, it shows how cultural values and practices and individual needs are critical aspects that should be considered in developing strategic designs for shared spaces as well as in future related studies. Data for the study was derived through observation, survey and interview. Two pairs of Filipino male siblings and another two pairs of Filipino female siblings were the respondents of the research. Each pair had been sharing a bedroom mostly as students for at least two years so that lifestle patterns were essentially established snd evident. Based on the results, privacy and territorial boundaries were compromised in the shared bedrooms. Privacy was not evident since the respondents were unable to perform some activities that require porivacy without being disturbed, prompting them to seek privacy elsewhere in their house. Moreover, it was difficult for the pairs of siblings to perform activities at the same time while oth of them were in the bedroom. The bedrooms also lacked physical barriers that would designate private areas. Privacy in relation to personal belongings was not absolute but allocation of areas in shared furniture reduced potential intrusions. Except for the designated sleeping areas, territoriality was mainly evident through the designation and division of areas in shared furniture pieces. The bedrooms were too small for each sibling to claim territories for their own purposes. Seniority had the upper hand in the spatial dynamics of the shared bedrooms. Elder siblings usually made the decisions in relation to space use and owned more objects in the bedroom. This and the failure to perform basic activities inside the bedroom were the issues that resulted to conflicts. Performing some activities in other areas of the house provided the desired privacy that the respondents failed to achieve in their own bedrooms. Male and female siblings had similar perceptions on privacy and territoriality. Their issues and their manner of resolving conflicts were also the same. Courtesy and keeping an open communication line were their usual means of resolving issues. Filipino values played a key role in these coping mechanisms.
Thesis (BSCT)--University of the Philippies Diliman
Keywords: Bedrooms